2020
DOI: 10.3389/fimmu.2019.03023
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Immunological Landscapes Characterize Inherited and Sporadic Mismatch Repair Deficient Endometrial Cancer

Abstract: Around 30% of endometrial cancers (EC) are mismatch repair (MMR) deficient, mostly as a consequence of mutations acquired during tumorigenesis, but a significant minority is caused by Lynch syndrome (LS). This inherited cancer predisposition syndrome primes an anti-cancer immune response, even in healthy carriers. We sought to explore the intra-tumoral immunological differences between genetically confirmed LS-associated MMR-deficient (MMRd), sporadic MMR-deficient, and MMR-proficient (MMRp) EC. Endometrial tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 46 publications
(57 reference statements)
6
44
0
Order By: Relevance
“…However, there was no stratification of MSI-H EC tumors according to their sporadic or inherited Lynch syndrome (LS) origins. Since MSI-H tumors display an increased immunogenicity compared with MSS tumors, some authors have investigated differences in immune cell populations between sporadic and LS MSI-H endometrial cancer, showing that these two groups are distinct immunological entities with different types of immune cells in stroma and tumor, respectively [ 65 , 66 ]. In conclusion, given the evident benefit found in MSI-H/MMRd cancer patients treated with immune checkpoint inhibitors, all EC patients should be tested to define the MMR status at the time of diagnosis, including the immune-infiltrate and the expression of PD-1 and PD-L1, in order to establish their future eligibility for immunotherapy treatment [ 67 , 68 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, there was no stratification of MSI-H EC tumors according to their sporadic or inherited Lynch syndrome (LS) origins. Since MSI-H tumors display an increased immunogenicity compared with MSS tumors, some authors have investigated differences in immune cell populations between sporadic and LS MSI-H endometrial cancer, showing that these two groups are distinct immunological entities with different types of immune cells in stroma and tumor, respectively [ 65 , 66 ]. In conclusion, given the evident benefit found in MSI-H/MMRd cancer patients treated with immune checkpoint inhibitors, all EC patients should be tested to define the MMR status at the time of diagnosis, including the immune-infiltrate and the expression of PD-1 and PD-L1, in order to establish their future eligibility for immunotherapy treatment [ 67 , 68 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…These interact with activated T-lymphocytes and thereby trigger a potentially strong antitumor immune response in the tissue. Accordingly, recent studies found LS EC to be highly immunogenic [ 123 , 124 ].…”
Section: Clinical Implications and Managementmentioning
confidence: 99%
“…Similarly, Ramchander et al reported a significantly elevated number of CD8-positive T cells in the invasive margin of LS-associated MSI ECs compared to sporadic cases. The same tendency was observed in the tumor center but failed to reach statistical significance [53]. Furthermore, another study reported a higher frequency of PD-L1 expression in LS-associated MSI ECs, compared to sporadic MSI ECs [65].…”
Section: Immune Infiltration In Hereditary and Sporadic Ecsmentioning
confidence: 68%
“…We first compared the immune infiltration determined by the quantitative analysis of different immune markers (CD3, CD4, CD8, PD1, PD-L1, FoxP3, CD45) between hereditary and sporadic MSI cancers. Seven studies [47][48][49][50][51][52][53] were informative for quantitatively evaluating the extent of local immune infiltration in MSI CRCs (Table 1). We looked at the results from the immunohistochemical analysis of different T cell subsets of these studies, where a total of 122 hereditary MSI CRC and 145 sporadic MSI CRC samples were examined.…”
Section: Immune Infiltration In Hereditary and Sporadic Msi Crcsmentioning
confidence: 99%